Speedy Wifi, A TELKOM'S Business Strategy to Compete in Broadband Internet Access Business in Bandung - Sari, Lidya; Soedjarno, Alibasjah Inggriantara (The Indonesian Journal of Business Administration, 2013)
Currently the Internet is not regarded as a luxury, but it has been regarded as a primary need. This resulted in a change in lifestyle people who are looking for cheap internet access service, fast, and of course can be accessed wherever and whenever they want. Telkom Speedy (Speedy) is one of the flagship products from PT. Telkom, which provide Internet access service to the people of Indonesia. In 2011 ago, the average sales and customer sales increased significantly. Only in 2012 was not as good performance achieved in the previous year. To find out the root cause of this problem external and internal analysis is done. External analysis divides into macro and micro environment. Macro environment is using PEST. While micro environment is using porter five forces. The general summary of macro environment is a changing of people lifestyle in doing internet access, while for micro environment is a high competition between internet service providers. For internal analysis is by doing analysis of Speedy product, which the result is Speedy offers high and stable speed access internet but couldn’t use in mobile. From the results of this analysis inferred that Speedy couldn’t answer the changing of lifestyle that happened in the market. The solution to the above problem was found by adjusting the analysis of strengths, weaknesses, opportunities and threats of the company (SWOT) and Porter Generic strategy options. The chosen strategy is cost leadership with product release Speedy WiFi. In addition Telkom has the power in the financial and sales channel distribution strategy is another reason why it was chosen because Speedy WiFi using existing network that already exists and wireless modem that has been installed on the customer side so it does not require an expensive cost. Segment to be addressed by Speedy WiFi are existing phone customers, potential customers phones, mobile internet subscribers, and new internet users. While the target to be addressed now is Telkom Speedy and existing customers from competitors. Positioning to be delivered from this product is a service to Internet users both normal and advanced users who need high speed internet and stable anytime, anywhere full of content and an affordable price. To maximize the sales of these products, promotional activities carried out above and below the line. The choice of a media campaign in which television, radio, print media, visits to educational institutions, offices institutions, communities, and doing canvassing Key Words: Telkom Speedy, Speedy WiFi